DNA barcoding on marine invertebrates - Hikam, Agus Mohammad; Mubarakati, Nurul Jadid; Dailami, Muhammad; Toha, Abdul Hamid A. (Jurnal Biologi Udayana, 2021)
A large number of species of marine invertebrates that have similar morphology cause misidentification very possible. Molecular species identification is important in taxonomy study accurately. This study aims to determine the identity of Aquatic Papua marine invertebrates with DNA barcoding technique using markers COI gene (Cytochrome c oxidase I). The study identified 29 individuals of marine invertebrates, which came from sea cucumbers (6 samples), lobsters (6 samples), octopus (6 samples), chitons (5 samples), and sea urchins (6 samples). Molecular identification methods consist of DNA isolation, PCR COI gene fragments, sequencing, and DNA sequence analysis using bioinformatics software. The results showed that the sea cucumber came from the Bohadschia marmorata species, the lobster came from the Panulirus versicolor species, the octopus came from the Octopus cyanea species, the chiton came from the Ischnochitonaustralis species, and the sea urchins came from the Tripneustesgratilla species. The similarity of samples and references are in the range of 84.58 to 100.00%. The disparity index, genetic distance, and phylogenetic tree supported this result.